2018
DOI: 10.1002/arch.21444
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin‐mediated recovery from bacteremia delays larval development in fall armyworm, Spodoptera frugiperda

Abstract: Insect immunity includes a surveillance system that detects and signals infections, coupled with hemocytic and humoral immune functions. These functions are signaled and coordinated by several biochemicals, including biogenic amines, insect cytokines, peptides, and prostaglandins (PGs). The actions of these mediators are coordinated within cells by various forms of cross-talk among the signaling systems and they result in effective reactions to infection. While this is well understood, we lack information on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…It was hypothesized to enhance immune responses in diseased insects since reduced lipid intake decreases hemolymph lipid concentration, which increases available apolipophorin III for pathogen recognition ( Adamo et al 2010 ). In general, these results were consistent with a recent study, in which the recovery from Serratia marcescens infection increased larval development time, decreased pupal mass, and decreased adult eclosion rate in Spodoptera frugiperda ( Zhang et al 2018 ). Thus, growth inhibition may be a common sublethal effect of bacterial infections in lepidopteran insects.…”
Section: Discussionsupporting
confidence: 92%
“…It was hypothesized to enhance immune responses in diseased insects since reduced lipid intake decreases hemolymph lipid concentration, which increases available apolipophorin III for pathogen recognition ( Adamo et al 2010 ). In general, these results were consistent with a recent study, in which the recovery from Serratia marcescens infection increased larval development time, decreased pupal mass, and decreased adult eclosion rate in Spodoptera frugiperda ( Zhang et al 2018 ). Thus, growth inhibition may be a common sublethal effect of bacterial infections in lepidopteran insects.…”
Section: Discussionsupporting
confidence: 92%
“…Yajima et al (2003) showed that the PLA 2 activity is associated with IMD immune signaling to produce AMPs in Drosophila. Furthermore, Zhang et al (2018) showed that PGs rescued Spodoptera frugiperda larvae infected with an entomopathogen, Serratia marcescens.…”
Section: Discussionmentioning
confidence: 99%
“…In the honey bee, immune challenge reduces expression and accumulation of stored plasma proteins such as vitellogenin and hexamerin, whereas it highly induces immune-associated genes, defensin and prophenoloxidase, suggesting an adaptive strategy to redirect resources to combat injury or infection (Lourenço et al, 2009). In S. frugiperda, in which PGs played a crucial role in mediating cellular immune response, the PG-treated larvae suffered reduced survivorship compared with controls (Zhang et al, 2018), indicating a fitness cost. Thus, PGE 2 is crucial for S. exigua survivability, but the excessive amount may impose to reduced pupal mass and adult fecundity owing to a trade-off effect.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other insect species, in which nodules are similar in size and can be directly counted [4], the nodules in fall armyworms are highly variable in size. To record nodules for this paper, we counted Indexed Nodules (IN) following the method of Zhang et al [20]. In detail, we recorded the diameters of each nodule, which occurred in a size range of about 20 to over 200 µm.…”
Section: Behavioral Fevers Led To Reduced Nodulation Reactionsmentioning
confidence: 99%